Accessibility evaluation of the playground during the play of children with cerebral palsy in school - Rocha, Aila Narene Dahwache Criado [UNESP]; Desidério, Sara Vieira [UNESP]; Massaro, Munique [UNESP] (FapUNIFESP (SciELO), 2018)
In the school context, the playground is an important place for children to participate in recreational activities. Through play, children acquire knowledge, they develop skills and abilities, they can feel pleasure and express their feelings. However, for the playground to promote the development of children, it must be accessible and safe for all children, including those with disabilities. The aim of this research was to evaluate the accessibility of a school playground of Early Childhood Education and also to analyse the participation of children with cerebral palsy in recreational activities developed in it. The participants were three children with cerebral palsy, from four to six years old, from a school of Early Childhood Education in a municipality of São Paulo - Brazil. Data collection was divided into two stages: 1) evaluation of the accessibility of the playground using the Protocol for evaluation of physical accessibility in Early Childhood Education schools; 2) observation of children with cerebral palsy during play activities in the playground. It was noted that the playground is not accessible for children with cerebral palsy. However, they participated in activities with the help of teachers and caregivers. The lack of adequate recreational equipment may have hindered the best performance of the children in school playground activities. It is necessary to educate professionals to increase the participation of children during play activities and to adequate the playground, making it accessible and safe for all children, as it is proposed by the Universal Design.
Avaliação da acessibilidade do parque durante o brincar de crianças com paralisia cerebral na Escola
Keywords: Accessibility; Cerebral palsy; Playground; Special education